The elector's guide. Conducted by a Committee of Yorkshire-men. No. 1-7 (1 vol.) (Bolland, 1826)
Addressed to the freeholders of the county of York. Pages 19-20 of no. 3 are missing. 1: The "Catholic Question". - 3rd ed. - 7 p.